Od wolności w literaturze do wolności na uniwersytecie - Popiel, Jacek (Przestrzenie Teorii, 2023)
Fiction literature and philosophical texts can remarkably influence contemporary understanding of freedom. The article discusses this subject, by analyzing selected texts, written by Czesław Miłosz, Adam Zagajewski, Zbigniew Herbert, Józef Tischner, Wiesław Myśliwski. Historical events, mentioned in texts, took place during the 1970’s and the 1980’s and were associated with the Jagiellonian University.